Pengendalian Kualitas Palet Kabel Kayu Berbahan Limbah Sisa Log dengan Integrasi Seven Tools dan QFD - Lilis Nurhayati; David Andrian (Universitas Sarjanawiyata Tamansiswa, 2026)
The utilization of log residue waste as an alternative raw material in the wood processing industry has the potential to improve resource efficiency; however, material heterogeneity often leads to product quality issues. This study aims to identify the dominant types of defects and their contributing factors in wooden cable pallets made from log residue waste, as well as to determine quality improvement priorities through the integration of Seven Tools of Quality and Quality Function Deployment (QFD). The study was conducted at UD Nurari Perdana Kabelindo, Sidoarjo, using production and defect data collected during September 2025 through observations, interviews, documentation, and questionnaires. The Seven Tools analysis employed check sheets, Pareto charts, and cause-and-effect diagrams to identify dominant defects and their root causes. The results were subsequently integrated into QFD through the development of a House of Quality to translate customer needs into priority technical characteristics. Customer requirements were determined based on product quality attributes obtained from 30 customer respondents using a census method. The results showed a defect rate of 11.51% of total production, with the dominant defects consisting of thickness deviation, wavy surfaces, knot defects, and asymmetrical circular shapes. The QFD analysis revealed that operator precision and raw material selection were the top priorities for quality improvement. These findings demonstrate that the integration of Seven Tools and QFD is effective in linking process defect analysis with customer needs to support sustainable product quality control.